Flavor deterioration of Mandarin juice during storage by MDGC-MS/O and GC-MS/PFPD. (1st April 2022) - Cheng, Yujiao; Li, Guijie; Wu, Houjiu; Liang, Guolu; Wang, Hua
Abstract: Commercial mandarin juice often exhibits flavor deterioration during storage. The changes in volatile flavor profiles were investigated in mandarin juice stored under three different temperature conditions (4 °C, 25 °C, and 40 °C). The application of multidimensional gas chromatography-mass spectrometry/olfactometry (MDGC-MS/O) coupled with aroma extract dilution analysis (AEDA) identified 31 odorants in stored mandarin juice, including seven off-flavor contributing compounds: methanethiol (unpleasant, repulsive), dimethyl sulfide (sulfur, cabbage), methional (cooked potato), p -cymene (solventy), 4-vinylguaiacol (medicine), terpinen-4-ol (wood), and α-terpineol (floral, mint). 4-Vinylguaiacol was also identified in mandarin juice for the first time. In addition, 64 volatile compounds determined by GC-MS/pulsed flame photometric detector (GC-MS/PFPD) were classified as alcohols, terpenes, volatile sulfur compounds (VSCs), aldehydes, esters, ketones, and phenols. Volatile compound differences were observed in mandarin juice under different storage conditions by heat-map generation and principal component analysis (PCA). The results revealed that high-temperature storage led to a rapid increase in the concentration of total alcohols and VSCs. Furthermore, the flavor deterioration markers α-terpineol and dimethyl sulfide were identified based on off-flavor contribution and variable importance in projection (VIP) (score >1) values in the PLS-DA model. These two compounds are valuable for marker-assisted flavor deterioration analysis in mandarin juice during storage. Graphical abstract: Image 1 Highlights: GC-MS/PFPD and MDGC-MS/O were applied to comprehensively determine volatiles in mandarin juice. Seven off-flavor contribution aroma-active compounds were found in mandarin juice. 4-Vinylguaiacol was identified for the first time in stored mandarin juice by AEDA. Changes in volatile profiles in stored mandarin juice were investigated by heat-map and PCA. Dimethyl sulfide and α-terpineol were selected as flavor deterioration markers.